Forest Fire Detection Using Wireless Sensor Network - Indu Priya R., Ria George, Nisha Naveen, Dayita Banerjee, Alla Srija (International Journal of Modern Agriculture, 2021)
A forest has various types of vegetation like herbs, trees, shrubs, and many species of animals. The renewables that are necessary to human beings. Forest fires are one of the common disasters in forests that lead to serious loss of forest wealth, biodiversity and the natural environment. Early observation and prevention measures need to be taken to protect forests from fires. To overcome this and prevent them, there are two most used traditional methods of human surveillance. First, is directly observed by human vision. The other is observation far away, by which one can achieve surveillance through a hardware approach of detection. In this paper, we are introducing an automated fire alert system that consists of two sensors, namely fire and smoke. These sensors detect a change in a physical environment and help in the early detection of a forest fire. The main characteristic of this fire detection system is to alert the user by using location detection and GSM module, whenever a fire is detected.